Festival fun - Blackburn, Rachel; Blackburn, Rachel Rachel Anne; Shortland Publications (Auckland, New Zealand Shortland Publications, 2000)
This book introduces children to a variety of festivals celebrated around the world including Diwali, Christmas, Chinese New Year. Through fun facts, vivid images, and simple descriptions, young readers explore cultural traditions in an engaging and age-appropriate format.
Includes colourful illustrations and photographs to support the text.
Primary grades (ages 5-8) Ideal for early years, especially Kindergarten and Grade 1 readers.
Keywords: Festivals-Holidays-Multicultural education-Children's literature